PERAN GENDER DALAM PENGAMBILAN KEPUTUSAN PADA MUSAWARAH PERENCANAAN PEMBANGUNAN (STUDI KASUS KECAMATAN MAIWA KABUPATEN ENREKANG) - Jawaria; Nonci, Nurjannah; D, Herman (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Women often face discrimination or patriarchal barriers in their involvement in decision-making related to development. Despite efforts to improve gender equality for women and encourage women's inclusion in various fields, there are still negative perceptions and stereotypes that hinder their participation. This research uses qualitative methods by conducting interviews to collect the necessary data. The informants in this study were as many people as PKK mothers, women's farmer groups and Posyandu cadre mothers. The analysis used to process data is by using Nvivo 12 Plus Software and Nvivo 12 Plus.. The results of the research using the Gender Framework Analysis (GFA) analysis technique show that the role of gender in decision making at the development planning meeting in Maiwa District is still low, this causes the amount of women's participation to be minimal, for example, the presence of women in Maiwa District is still low from the total number of participants. Even though the number of women's attendance is low in the forum, these women are not only present but also active by providing a lot of input in the forum. The role of gender in decision-making at the development planning meeting in Maiwa Sub-district is still lacking, which causes the level of women's participation in musrenbangkec to still experience high obstacles, namely 38.89% and the indicator of stigma in participation, namely 36.36%. The lack of women's involvement in decision-making is also due to their own factors and the stigma that has been embedded in them.